Visualization of the human body by using 3D technologies in the study of "Human anatomy" in medical universities - Murzina, O. A.; Hrinivetska, N. V.; Matvieishyna, T. M.; Vovchenko, M. B.; Sherbacov, M. S.; Мурзіна, Олена Анатоліївна; Грінівецька, Наталія Валеріївна; Матвєйшина, Тетяна Миколаївна; Вовченко, Михайло Борисович; Щербаков, Максим Степанович (My University, 2023)
The article examines the possibilities of using the latest forms and methods of teaching students in the basic discipline «Human Anatomy» at the stage of preclinical professional training of future doctors of various specialties in institutions of higher medical education. The important role of combining classical approaches in studying the basic discipline with innovative technologies such as digital library, digital textbooks, test systems, simulators, expert systems, interactive anatomical table and 3D ORGANON is emphasized. And the advantages of using 3D anatomy visualization and virtual dissection, such as an ability to put a virtual marker and text fragments, which can be used during a lesson on a digital presentation of a body or an organ with the function of saving and fixing, are also considered. The interactive anatomical table helps to avoid prior contact of an unprepared student with a real corpse, and due to regular software updates via the Internet, future doctors always receive up-to-date information. В статті розглянуто можливості використання в закладах вищої медичної освіти новітніх форм та методів навчання студентів з базової дисципліни «Анатомія людини» на етапі доклінічної професійної підготовки майбутніх лікарів різних спеціальностей. Підкреслено важлива роль поєднання класичних підходів у вивченні базової дисципліни з інноваційними технологіями такі як, цифрова бібліотека, цифрові підручники, тестові системи, тренажери, експертні системи, анатомічний стіл та 3D ORGANON. А також розглянуто переваги використання 3D анатомічного столу такі як віртуальний маркер та текстові фрагменти, які можна використовувати під час заняття над зображенням тіла або органу з функцією збереження і закріплення. 3D анатомічний стіл допомагає уникнути попереднього контакту непідготовленого студента з реальним трупом та завдяки регулярному оновленню програмного забезпечення через Інтернет, майбутні лікарі завжди отримують актуальну інформацію.
Використання візуалізації тіла людини за допомогою 3D технологій при вивченні «Анатомії людини» в медичних університетах.
Murzina O. A. - https://orcid.org/0000-0002-6968-5525; Hrinivetska N. V. - https://orcid.org/0000-0001-9642-0285; Matvieishyna T. M. - https://orcid.org/ 0000-0002-9078-9580; Vovchenko M. B. - https://orcid.org/ 0000-0002-8838-2757; Sherbacov M. S. - https://orcid.org/0000-0001-5776-8182.
Keywords: the interactive anatomical table; 3D ORGANON; the latest innovative teaching methods; media environment; media competence; 3D анатомічний стіл; новітні інноваційні методи навчання; медіасередовище; медіакомпетентність